Habitat specialization predicts genetic response to fragmentation in tropical birds. Issue 16 (29th July 2016) - Khimoun, Aurélie; Eraud, Cyril; Ollivier, Anthony; Arnoux, Emilie; Rocheteau, Vincent; Bely, Marine; Lefol, Emilie; Delpuech, Martin; Carpentier, Marie‐Laure; Leblond, Gilles; Levesque, Anthony; Charbonnel, Anaïs; et al.
Abstract: Habitat fragmentation is one of the most severe threats to biodiversity as it may lead to changes in population genetic structure, with ultimate modifications of species evolutionary potential and local extinctions. Nonetheless, fragmentation does not equally affect all species and identifying which ecological traits are related to species sensitivity to habitat fragmentation could help prioritization of conservation efforts. Despite the theoretical link between species ecology and extinction proneness, comparative studies explicitly testing the hypothesis that particular ecological traits underlies species‐specific population structure are rare. Here, we used a comparative approach on eight bird species, co‐occurring across the same fragmented landscape. For each species, we quantified relative levels of forest specialization and genetic differentiation among populations. To test the link between forest specialization and susceptibility to forest fragmentation, we assessed species responses to fragmentation by comparing levels of genetic differentiation between continuous and fragmented forest landscapes. Our results revealed a significant and substantial population structure at a very small spatial scale for mobile organisms such as birds. More importantly, we found that specialist species are more affected by forest fragmentation than generalist ones. Finally, our results suggest that even a simple habitat specialization index can be a satisfying predictor of genetic and demographic consequences of habitat fragmentation, providing a reliable practical and quantitative tool for conservation biology.